2016
DOI: 10.1111/cch.12437
|View full text |Cite
|
Sign up to set email alerts
|

A narrative meta‐review of a series of systematic and meta‐analytic reviews on the intervention outcome for children with developmental co‐ordination disorder

Abstract: Although the quality of the reviews progressively improved over the years, the shortcomings identified need to be addressed before concrete evidence regarding the best approach to intervention for children with DCD can be specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…However, as a number of the studies presented different treatments, it was therefore difficult to establish one single recommendation for children with DCD. These results were similarly reported in the meta-review proposed by Miyahara et al (2017), in which all included systematic reviews concluded that some kind of intervention was better than none at all, however they stated that concrete evidence regarding the best approach to intervention for children with DCD still needs to be specified. Motor skill competence is defined as proficiency in fundamental motor skills (Stodden et al, 2008), including the categories of locomotor skills, object control and balance.…”
Section: Leemrijse Et Al (2000) (Netherlands) -Rctsupporting
confidence: 60%
See 2 more Smart Citations
“…However, as a number of the studies presented different treatments, it was therefore difficult to establish one single recommendation for children with DCD. These results were similarly reported in the meta-review proposed by Miyahara et al (2017), in which all included systematic reviews concluded that some kind of intervention was better than none at all, however they stated that concrete evidence regarding the best approach to intervention for children with DCD still needs to be specified. Motor skill competence is defined as proficiency in fundamental motor skills (Stodden et al, 2008), including the categories of locomotor skills, object control and balance.…”
Section: Leemrijse Et Al (2000) (Netherlands) -Rctsupporting
confidence: 60%
“…According to Miyahara et al (2017) in the current Era of evidence-based medicine, systematic reviews and metaanalyzes sit at the top of the hierarchy of research designs employed to evaluate the strength of evidence in support of a particular intervention approach. Previous systematic reviews and meta-analyses on interventions that aim to improve motor performance of children (Pless and Carlsson, 2000;Morgan and Long, 2012;Smits-Engelsman et al, 2013) used rating scales as a method for assessing the quality of evidence, which may not adequately reflect the risk of bias contained within the articles, therefore its use is not recommended in the methodology for conducting systematic review (Greenland, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search and selection procedure followed the protocol of the first meta‐review (Miyahara, Lagisz, et al, 2017) (see Data S1 for search and section strategy) . Any inconsistencies in the search results and selection between the first author and a subject librarian were resolved through subsequent collaborative search, reading of respective journal articles and discussion.…”
Section: Methodsmentioning
confidence: 99%
“…Keeping up with an ever increasing number of primary research studies is almost impossible for service consumers, practitioners and policymakers (Bastian, Glasziou, & Chalmers, 2010). In 2017, the first tertiary (para level) review was published in which Miyahara, Lagisz, Nakagawa and Henderson (2017) used the first edition of the Assessment of Multiple Systematic Reviews (AMSTAR; Shea et al, 2007) to assess the four existing secondary reviews. By highlighting a number of weaknesses in the methodology employed, these authors were able to show that the conclusions drawn from the secondary reviews were not as solid as their authors had claimed.…”
Section: Introductionmentioning
confidence: 99%